Pandangan Medis Mengenai Perintah Mandi Wajib Dalam Islam - Elfata Shafa Azzahra; Nadhya Azkiah Fawwaz; Nasywa Felisha Putri Fahlevi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research explains the practice of obligatory bathing in Islam, including after sexual intercourse, after childbirth, menstruation, semen discharge, and on corpses. Obligatory bathing is an integral part of maintaining ritual purity and cleanliness in Islam, carried out to eliminate major hadats. The research method is descriptive analysis based on primary and secondary data sources. Obligatory bathing after releasing semen cleanses the body and has physical and psychological health benefits. Obligatory bathing after sexual intercourse is an important hygiene practice and marks readiness for religious worship. Obligatory bathing after menstruation and childbirth allows women to return to religious practices after a certain period. Obligatory bathing of the corpse is an act of respect and preparation of the corpse before wearing the shroud and burial. Medically, bathing after giving birth helps cleanse the body and reduces the risk of postpartum infections. This research provides a comprehensive understanding of the practice of obligatory bathing in Islam, its purpose, benefits, and implications.